3(x+1)=5(x-2)

Simple and best practice solution for 3(x+1)=5(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+1)=5(x-2) equation:


Simplifying
3(x + 1) = 5(x + -2)

Reorder the terms:
3(1 + x) = 5(x + -2)
(1 * 3 + x * 3) = 5(x + -2)
(3 + 3x) = 5(x + -2)

Reorder the terms:
3 + 3x = 5(-2 + x)
3 + 3x = (-2 * 5 + x * 5)
3 + 3x = (-10 + 5x)

Solving
3 + 3x = -10 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
3 + 3x + -5x = -10 + 5x + -5x

Combine like terms: 3x + -5x = -2x
3 + -2x = -10 + 5x + -5x

Combine like terms: 5x + -5x = 0
3 + -2x = -10 + 0
3 + -2x = -10

Add '-3' to each side of the equation.
3 + -3 + -2x = -10 + -3

Combine like terms: 3 + -3 = 0
0 + -2x = -10 + -3
-2x = -10 + -3

Combine like terms: -10 + -3 = -13
-2x = -13

Divide each side by '-2'.
x = 6.5

Simplifying
x = 6.5

See similar equations:

| 2x+14y=-6 | | 320=1/5(1500+x) | | 8-6w=-37 | | 2x+3y-4= | | 3(3x+1)-(x+1)=(6x+10) | | 4v-36=-8(8+3v) | | -2x+14=8x-46 | | 7(x-2)=39.2 | | 4(a+2)=34.4 | | x+2x=6x+2 | | 31.6=7c-2 | | -4(-4v+1)-6v=2(v-7)-2 | | -3y+15+y=39 | | 33-5x=-8+-48x-2 | | 2x^7-7=-25 | | -2x+6=-6 | | 8x-2=46.8 | | 4x=15.2 | | 8t+7=32 | | (x+11)2-72=0 | | 5+16w=6-45 | | 2.9x-4.8+2x=2.4+3.3-10.6 | | (x-4)2-20=0 | | 6(1x+-5)=2(10+3x) | | (x+1)2-18=0 | | (x-7)2-19=0 | | 24-8k=-7k | | 4.9(4+3x)-7.6=12 | | 2x-8+2=1 | | (x+11)2-11=0 | | -z+1=z-1 | | 0.13x-0.52=1.48x-3.523 |

Equations solver categories